NUMERICAL 3D ANALYSIS OF BURIED FLEXIBLE PIPELINE - Kliszczewicz, Barbara (European Scientific Journal, ESJ, 2013)
The subject of the analysis is soil interaction of a PVC flexible pipeline with its surface loaded uniformly across a certain area. When such an interaction is taken into account in classical calculations, soil is usually replaced with a largely simplified analogue (a system of vertical and horizontal pressure) and a spatial pipeline structure is replaced with a pipe ring representing a characteristic cross-section of a pipe in the plane state of strain (2D model). With such an approach, the considered calculation scheme is naturally far from the reality. Unlike analytical calculations, numerical analyses allow to take into consideration the spatial character of a pipeline laid in the ground (a 3D model of a pipe-soil system). Numerous factors may be additionally included influencing the scope and character of interaction between a pipe and soil, such as pipe deformability resulting from a pipeline’s material parameters, a method of incorporating a pipeline into the soil (excavation and non-excavation methods) or load increase in time. The article presents the assumptions, programme and results of a 3D numerical analysis of a pipe-soil system model undertaken with Z_Soil software. The model analysed consists of a rectilinear section of a PVC pipe and the surrounding mass of strongly stratified soil. The pipe is modelled according to its flexibility, while an elastic-plastic model was applied for soil modelling with Hardening Soil – Small isotropic strengthening considering a non-linear change in soil stiffness for small strains (10-6 – 10-3). It is essential to take such variable soil stiffness into account in modelling the structure-to-soil interaction. The outcomes of the analysis performed are presented mainly graphically by listing the maps of model deformation, maps of stress and strain of the soil mass and pipe structure and diagrams of characteristic displacements of pipe points, and the diagrams of generalised internal forces in a pipeline.